FTVI promotes osteogenic differentiation of bone marrow mesenchymal stem cells through LncRNA HIF1A-AS2 - Xiao, Fei; Wang, Zidan; Cheng, Keke; Xing, Haiyuan; Lei, Tianrun; Wang, Junwen (Journal of orthopaedic surgery and research, 2025)
The treatment of bone defects caused by trauma and pathological factors was a common problem in clinic. Extracorporeal fucosylation has been proved to promote osteogenic differentiation. Nevertheless, the biological processes by which they promote osteogenesis are currently poorly understood. Long non-coding RNAs (lncRNAs) were essential for controlling osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). This study aimed to investigate whether LncRNA HIF1A-AS2 could mediate the effects of alpha-(1,3)-fucosyltransferase VI (FTVI) on osteogenic differentiation of BMSCs. Rat BMSCs with lncRNA HIF1A-AS2 interference plasmid or the FTVI overexpression plasmid were co-cultured in osteogenic differentiation medium. The effects of fucosylation modification of FTVI on osteogenic differentiation of BMSCs were examined, with a focus on LncRNA HIF1A-AS2. FTVI could upregulate HIF1A-AS2, and inhibition of lncRNA HIF1A-AS2 in FTVI- transfected BMSCs could decrease type I collagen (Col I), runt-related transcription factor 2 (RUNX2), osteocalcin (OCN) and bone morphogenetic protein 2 (BMP2), vascular endothelial growth factor 165 (VEGF165) proteins expressions which were increased by FTVI. Furthermore, it was discovered that inhibiting lncRNA HIF1A-AS2 decreased the the homing ability of BMSCs demonstrating by antigen contents of HECA452 and CD15s. According to these results, the effects of FTVI on osteogenic differentiation of BMSCs depend on the existence of lncRNA HIF1A-AS2. A better understanding of the pathophysiological mechanism of bone defect helped to provide theoretical basis for the reconstruction of bone damage using stem cells in clinic.